2021
DOI: 10.1126/sciadv.abg1512
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic organization of striatum is linked to cortical activity and brain expression of genes associated with psychiatric illness

Abstract: Dopamine signaling is constrained to discrete tracts yet has brain-wide effects on neural activity. The nature of this relationship between local dopamine signaling and brain-wide neuronal activity is not clearly defined and has relevance for neuropsychiatric illnesses where abnormalities of cortical activity and dopamine signaling coexist. Using simultaneous PET-MRI in healthy volunteers, we find strong evidence that patterns of striatal dopamine signaling and cortical blood flow (an index of local neural act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 86 publications
1
13
2
Order By: Relevance
“…It is also worth noting that this study found the highest degree of amphetamine-induced dopamine release in the limbic striatum, contrary to more recent studies [45]. The neuromodulatory effects of dopamine signaling from the striatum are shown to affect distal cortical regions [176][177][178][179]. These findings highlight the key role of the corticostriatal circuitry in the regulation of functional brain networks.…”
Section: Correspondence With In Vivo Dwi and Functional Imaging Studiescontrasting
confidence: 94%
“…It is also worth noting that this study found the highest degree of amphetamine-induced dopamine release in the limbic striatum, contrary to more recent studies [45]. The neuromodulatory effects of dopamine signaling from the striatum are shown to affect distal cortical regions [176][177][178][179]. These findings highlight the key role of the corticostriatal circuitry in the regulation of functional brain networks.…”
Section: Correspondence With In Vivo Dwi and Functional Imaging Studiescontrasting
confidence: 94%
“…Intriguingly, TAAR1 has also been shown to impact pre-and post-synaptic glutamatergic neurotransmission in the striatum of rodent Parkinson's disease models [144]. The ability to regulate corticostriatal crosstalk is not only of relevance to Parkinson's disease, but also schizophrenia and other psychiatric disorders [145]. Moreover, TAAR1 may participate in glutamate clearance via modulation of the excitatory amino acid transporter 2 (EAAT2) [146,147].…”
Section: Development Of Synthetic Taar1 Ligandsmentioning
confidence: 99%
“…We sought to test this hypothesis by using combined PET-magnetic resonance (MR) imaging to simultaneously measure both NMDAR availability in the hippocampus and glutamate levels in the striatum. In addition, given the evidence to support the involvement of fronto-striatal interactions in schizophrenia (McCutcheon et al, 2021) and to assess the specificity of the relationship between hippocampal NMDAR and striatal glutamate, we included an exploratory analysis to determine whether there is an association between frontal NMDAR availability and striatal glutamate levels.…”
Section: The Association Between N-methyl-d-aspartate Receptor Availa...mentioning
confidence: 99%
“…Our finding that lower hippocampal NMDAR availability is associated with higher striatal glutamate levels provides further evidence that hippocampal dysfunction is linked to the function of the striatum in psychosis (Adams et al, 2020; Lieberman et al, 2018; Stone et al, 2010). However, it should be recognised that this does not preclude the involvement of other circuit dysfunction in the illness as well (McCutcheon et al, 2021).…”
Section: Interpretation and Implications For The Pathophysiology Of P...mentioning
confidence: 99%